Education in times of climate change: Easing learning to build a climate-protection culture - Hernández, Francisco Heras (Mètode Revista de difusió de la investigació, 2015)
Climate change presents significant educational challenges: it is necessary to know about its causes, to recognise the roots of the problem and to be aware of its consequences. This is necessary to build a more realistic perception of climate risks and better understand our vulnerabilities. But it is especially important to know about the solutions; urgent training is needed to build a «low-carbon» culture to prevent dangerous interference with the global climate. Educational institutions – both formal and informal – must consider their contribution to these needs for knowledge and social change, because climate change will impact our future heavily and because everyone plays a role in the complex network of responsibilities that fuel it.

Not Just Hot Air: Putting climate change education into Practice - UNESCO (UNESCO Digital Library, 2015)